PERAN PENINGKATAN PENDIDIKAN JASMANI OLAHARAGA DAN KESEHATAN PADA SISWA SDN PENGEMBUR KECAMATAN PUJUT - L. Hasan Ashari; Zakir Burhan (LPPM Institut Pendidikan Nusantara Global, 2021)
The purpose of this study was to determine the level of student learning profcess at SDN Pengembur Elementary School. The method used in achieving these goals is to use data, observation and docomentation and perform analysis. The population in the study amounted to 26 students for the 100 m running sport which was specifically involved in class VI at SDN Pengembur. The learning outcomems of each assessment can score a percentage of the medium category oof pre-test 71.4 post-test 80 category of high KKM category is the pre-test 85 post-test 87.28.